EVALUATION OF PROTEIN AND IRON ABSORPTION OF MOCAF-BASED WEANING FOOD - Lia Ratnawati; Dewi Desnilasari; Novita Indriati; Enny Sholichah; Dita Kristanti (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2021)
Weaning food biscuit based on mocaf (modified cassava flour) with substitution of soybean, mung bean and red kidney bean flour is expected increasing protein of the product. However, in the legumes flour there are anti-nutritional agent that can affect the absorption of other nutrient such as protein and iron. The purpose of this study was to evaluate the absorption of protein and iron from mocaf based-weaning food. Protein and iron absorption were determined from weaning food (biscuit) using Sprague-Dawley rats, 3 weeks old, weight 70-80 g for 0, 30, 60, 90, and 120 minutes. The treatments of this study were mocaf biscuits (as a control), biscuits with substitution of soybean flour (MSF), mung bean flour (MMF), red kidney bean flour (MRF) and commercial biscuits (CB). The highest protein absorption of control, MSF and MRF were at 120 minutes with absorption percentages 27.76, 38.94, and 9.35%, respectively. Samples MMF and CB had the highest protein absorption at 60 and 90 minutes, with absorption percentages 15.58 and 37.57%. Meanwhile, the highest iron absorption of control, MSF and MMF were at 90 minutes with absorption percentages 53.86, 4.71, and 54.29%. Samples MRF and CB had highest iron absorption at 60 minutes with absorption percentages 7.97 and 69.76%, respectively. The MSF sample had highest protein absorption than other samples. Meanwhile, the MMF sample had an iron absorption value that approached to commercial biscuit.